Oral health problems profile in infants and preschool children attended at the dental emergency service of a children´s health centre of Brazil - Antunes, Roberta de Barros (2018)
Objective: To determine the profile of oral problems in infants and preschool children treated at an emergency service from Clinic of Infantile Specialities / Clinical Baby of the State University of Londrina, Brazil. Materials and method: Retrospective study where 776 clinical histories of patients aged 0 to 72 months, treated between April 2007 and April 2008 were analysed. Data collection included gender, age, place of residence, parental occupation and educational level, reason for consultation, involved teeth and performed intervention. Chi-square test (χ2) and a significance level of 5% were used for variables associations. Results: A greater proportion of male patients (55.5%) attended the service and the main age group was the 0-24 months (27.3%). It was found that 62.9% lived in urban areas and most parents/caregivers had completed secondary school (30.5% parents, 33.8% mothers). The main reason for consultation was caries (38.9%) - pain as main complaint (42.0%) and dental trauma (28.9%). The most affected tooth by caries was the lower second primary molar and, regarding trauma, the upper central primary incisors were the most injured. Interventions varied from endodontic treatment (16.0%) and adequacy of oral environment (15.1%). There was a statistically significant association between mother educational level and reason for consultation (p = 0.001). Conclusion: The assessed health service was necessary and useful. However, oral health problems resolution in the paediatric population in Londrina will only occur after the implementation of reorganised dental services from the currently available.